Parks Canada's National Marine Conservation Areas : Can we sink a ship in these waters to create an artificial reef and dive site? - Mowbray, Dawne (My University, 2015)
Current marine policy in Parks Canada indicates that creating an artificial reef for display purposes or sinking a vessel for recreational diving is not permitted in a national marine conservation area. Interviews and consultations of lawyers and experts in artificial reefs, environmental law, and Parks Canada policy were conducted; and historical and interpretive analyses of Parks Canada marine policy and domestic and international law were completed. The combined rich data was used to determine whether new marine policy developed under the recent National Marine Conservation Areas Act, 2002 could contain the same prohibition against sinking a ship or creating an artificial reef as the current policy. The results indicated that current policy trends seem to favour visitor experience, that the conservation mandate serves the "for the people" mandate, that the precautionary principle found within the NMCA Act is designed to change with societal norms, and that the NMCA Act itself does not prohibit the creation of an artificial reef provided it does not harm the marine ecosystem.
Keywords: Artificial reef; Canada National Marine Conservation Areas Act; Conservation and use; Marine policy in Parks Canada; Marine protected areas; National marine conservation areas